Effect of Water Stress on Morpho-physiological Parameters of Coriander (Coriandrum sativum L.) - Saxena, S N; Rathore, S S; Kakani, R K; Lal, G; Meena, R S; Singh, H; Singh, B (Annals of Arid Zone, 2016)
Twelve coriander accessions having released varieties, advance breeding material, regional and exotic collections were evaluated for effect of water stress on morpho-physiological and seed quality parameters. All accessions showed variability in ratio of fresh weight to dry weight, shoot length to root length, shoot weight to root weight, plant water relation parameters, total oil and essential oil. Water stress applied at flowering stage and terminal growth stage affected these parameters significantly in all accessions. There is high variability among accessions for their response to water stress which can be exploited for development of varieties for limited water conditions. Key words: Coriandrum sativum, coriander, morpho-physiological, total oil, essential oil, water stress.